Analysis of the ecological evolution of an area in the Setúbal Peninsula (Apostiça) caused by changes in land use patterns - Quinta-Nova, L.C. (2012)
Texto publicado no livro "Key Concepts in Landscape Ecology", editado por: J.W. Dover e R.G.H. Bunce (IALE-UK), correspondente aos Proceedings do Congresso Europeu da IALE em 1998.